Molecular recognition of an acyl-peptide hormone and activation of ghrelin receptor - Yue Wang (Nature Portfolio, 2021)
Ghrelin is a gastric peptide hormone and its acylation is required for binding to and activation of the ghrelin receptor in the brain, which initiates appetite. Here, the authors present cryo-EM structures of the Gq-coupled ghrelin receptor bound to ghrelin and the synthetic agonist GHRP-6 and they describe how the acylated peptide hormone is recognised by the receptor, which is of interest for drug design.